Investigating flush system method for minimum water usage of toilet system - Othman, Mohd Syafiq Salman (2014)
A major concern for most people these days is the use and availability of clean water. With 83 million more people on Earth each year, demands for clean water will keep on rising. Water is everywhere and also important to living things on Earth. But because of the global warming and pollution, water has become deficit in many parts of the world. It can be foreseen that one day water will become a very valuable asset for countries in the future as energy is now. In this study, focus will be given more on the effect of water tank designs in reducing the volume of water usage in toilet system. Testing was divided into two sections that were experimental study and simulation study. First, experimental study conducted to test the performance of four different types of tanks and results are recorded. After that, simulation study conducted and data was recorded. The parameters of the study were the effect of depth of water and design of the water tanks towards pressure and volume flow rate of the water. Based from the test results, comparison was calculated. With percentage error below than 5 percent, it has been determined that simulation study was indeed suitable for this study. To achieve the objectives of this study, the change in design of water tank was proposed to minimize the amount of water used without sacrificing the performance of the toilet. By modifying the water tank designs, the amount of water used inside the tank can be decreased. From simulation study that has been conducted for two design concepts, pressure exerted from the tanks only lost a little amount of energy. As conclusion, by changing the design of water tanks without changing the water level, one could help reduce the amount of water used for flushing his waste. At the same time, it will not affecting the performance of the whole toilet system.